Ikonografske opombe k Solčavski in Krakovski Mariji (Zbornik za umetnostno zgodovino (Nova vrsta), 1988)
The article considers the iconographic questions raised by the figure of the Virgin Mary in the parish church in Solčava (the Solčava Virgin) and the relief of the Virgin Mary from the old church in Krakovo (the Krakovo Virgin), which is now in the collection of the National Gallery in Ljubljana. Stylistically and iconographically these figures are among the most important monuments in Slovenia from the transition period from the Romanesque to the Gothic style (13th century). In the case of the Solčava Virgin there is an unusual gesture - the Virgin holds the Child's chin. On the basis of comparative material the author advances the hypothesis that this is a symbolic gesture which could reflect some beliefs and cults which were characteristic for the Middle Ages. In the case of the Krakovo Virgin the attention should be drawn to a number of mediaeval literary sources which could have influenced the iconographic composition of the Krakovo relief.